Relação solo-fitossociologia em um remanescente de floresta estacional decidual - Almeida, Clarice Maboni de (2010)
The study aimed at evaluating tree and shrub vegetation concerning the slope of the soil in Seasonal Deciduous Forest. The vegetation assessment was conducted in 14 plots systematically distributed in the forest and divided into subplots of 10 x 10 m, in which individuals with circumference 1.3 m of soil (CAP) ≥ 30 cm were observed. These individuals represented class I while individuals with a CAP ≥ 15 < 30 cm represented class II. Vegetation was analyzed by means of the TWINSPAN (Two-way Indicator Species Analysis) method to classify groups, within which the horizontal structure of the forest was studied. In 36 subplots, morphological description of the soil profile was carried out, samples were collected for chemical analysis and clay was determined at three depths (0-10, 10-20 and 20-30 cm), as well as slope, which was classified as low slope (1 ≥ 15), medium slope (15 ≥ 35) and high slope (≥35). The relationship between clusters of vegetation, slope and soil characteristics was studied by means of Principal Component Analysis (PCA). In G1, indicator species were Trichilia claussenii, Cupania vernalis and Crysophyllum marginatum and, in G2, Luehea divaricata and Sebastiania commersoniana. In terms of horizontal structure, these species were among the three best represented ones. Both clusters occurred in areas of variable slope, however, G2 took place in an environment which was more susceptible to interference in the vegetation. From PCA, it could be observed that soil characteristics and slope explained 26% of the total variability, and, out of these, 72% was explained in the main component 1, showing a strong correlation between soil characteristics and the presence of phytosociological groups in different slopes. This relationship is stronger for the presence of the two groups in the ranges of medium and high slope, on the other hand, in terms of low slope, the two groups showed no positive correlation with soil characteristics. For G1 in high slope and G2 in medium and high slope, correlation is positive concerning the whole characteristics of cationic exchange. However, G1 in medium slope was strongly correlated to the complex of exchangeable acidity. G2 at higher slopes also shows high correlation with clay, the finer texture may confer a greater degree of aggregation and reactivity, allowing the development of large species such as Luehea divaricata and Cordia americana. In general, due to restrictions of soil and slope, maintaining of the remnants is prior, aiming at important environmental services for the region.